Short and prolonged fasting prior to the performance of tracheostomies in intensive therapy: a retrospective study: Ayuno corto vs prolongado previo a la realización de traqueostomías en pacientes de terapia intensiva: un estudio retrospectivo - Duran, Lucas Gonzalo (2024)
Introduction: International guidelines on aid prior to invasive procedures usually generate longer aid than in intensive care (IT) patients. This fact represents a high risk of malnutrition and, consequently, a worse prognosis. The objective of the present investigation was to analyze the degree of association between the fasting time prior to tracheostomy of patients under mechanical ventilatory assistance (MVA) and the appearance of pneumonia. Methods: Retrospective cohort study that included patients admitted to our IT from 10/01/2018 to 08/31/2022 and with a tracheostomy performed. Two cohorts were defined characterized by fasting ≤3 hours vs. >3 hours. Fisher's exact test and Mann-Whitney test were used for bivariate analysis. A p value <0.05 was shown to be significant. Results: 141 patients were hospitalized with a tracheostomy, 9 were excluded, leaving 132 patients. The cohort with fasting ≤3 hours was made up of 15 patients and the one with fasting >3 hours was made up of 117, the latter presented an average fast of 2.5 hours (RI 2-3), days of AVM prior to the procedure of 13 days (RI 12-18), while the other cohort presented an average fast of 6 hours (RI 5-8), days of AVM prior to the procedure of 12 days (RI 10-14.5). When analyzing the association between the type of fasting and the appearance of pneumonia, an OR of 0.958 (95% CI: 0.32-2.87) was obtained, p value of 0.743. Conclusions: No significant differences were found regarding fasting time and the appearance of pneumonia as referred to in the international literature.